Preslip and cascade processes initiating laboratory stick slip. Issue 8 (1st August 2014) - McLaskey, Gregory C.; Lockner, David A.
Abstract Recent modeling studies have explored whether earthquakes begin with a large aseismic nucleation process or initiate dynamically from the rapid growth of a smaller instability in a "cascade‐up" process. To explore such a case in the laboratory, we study the initiation of dynamic rupture (stick slip) of a smooth saw‐cut fault in a 76 mm diameter cylindrical granite laboratory sample at 40–120 MPa confining pressure. We use a high dynamic range recording system to directly compare the seismic waves radiated during the stick‐slip event to those radiated from tiny (M −6) discrete seismic events, commonly known as acoustic emissions (AEs), that occur in the seconds prior to each large stick slip. The seismic moments, focal mechanisms, locations, and timing of the AEs all contribute to our understanding of their mechanics and provide us with information about the stick‐slip nucleation process. In a sequence of 10 stick slips, the first few microseconds of the signals recorded from stick‐slip instabilities are nearly indistinguishable from those of premonitory AEs. In this sense, it appears that each stick slip begins as an AE event that rapidly ( 20 µs) grows about 2 orders of magnitude in linear dimension and ruptures the entire 150 mm length of the simulated fault. We also measure accelerating fault slip in the final seconds before stick slip. We estimate that this slip is at least 98% aseismic and that it both weakens the fault and produces AEs that will eventually cascade‐up to initiate the larger dynamic rupture.